On a Rare Cutaneous Metastasis from a Sacrococcygeal Chordoma - Alessandro D'Amuri; Matteo Brunelli; Federica Floccari; Francesco De Caro; Giuliana Crisman; Francesca Sanguedolce; Marcello Filotico (Hindawi Limited, 2017)
Chordomas are rare malignant tumors of notochordal origin and are rare locally aggressive ones with a metastatic potential. The skin rarely is seen as metastatic site. We describe a case of an adult woman with cutaneous metastasis of a primary sacral chordoma excised ten years before, which appeared as a painless cutaneous mass located in the dorsal region. Once removed, the surgical specimen was formalin fixed and in paraffin embedded. Sections were stained with haematoxylin-eosin, and histochemical and immunohistochemical investigations were performed. Histologically, the neoplasia was characterized by cords or single tumor cells with an abundant myxoid stroma, conspicuous pale vacuolated cytoplasm (the classic "physaliphorous cells"), and mild nuclear atypia. Mitotic activity was scanty. At immunohistochemistry, the tumor cells were diffusely positive for S-100 protein, pan-keratins, EMA, and vimentin. A diagnosis of cutaneous metastasis of chordoma was performed. This case illustrates a diagnostic challenge because of the unusual presentation of an already rare tumor.